1976
DOI: 10.1007/bf00005745
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the gut contents of leptestheriella maduraiensis (Conchostraca: Branchiopoda) Nayar and Nair

Abstract: Studies on the food and feeding habits of Leptestheriella maduraiensis Nayar & Nair have shown that the organisms are nonselective algal and detrital filter feeders. They utilise available food in almost similar proportions as in the overlying pond water and it is found from the present studies that the phytoplankton (Bacillariophyceae, Chlorophyceae and Cyanophyceae) form the major part of the gut (48.9%), followed by detritus (38.6°%), zooplankton ( . %) and miscellaneous items ( .4%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Yet, it was also suggested that the crustacean remains might have been derived from exuvia floating in the water and not from living animals. A similar suggestion was also advanced by Royan (1976) for Leptestheriella (Conchostraca).…”
Section: Introductionsupporting
confidence: 75%
“…Yet, it was also suggested that the crustacean remains might have been derived from exuvia floating in the water and not from living animals. A similar suggestion was also advanced by Royan (1976) for Leptestheriella (Conchostraca).…”
Section: Introductionsupporting
confidence: 75%
“…Sometimes Notostraca can also be diggers and sifters of organic bottom material and feed on small animals like Tubificidae (Thiery, 1987). Spinicaudata are also omnivorous (Royan, 1976) but sometimes obtain food by scraping the periphyton attached to vegetation. As the source of food is diversified (benthic bacterial flocks, planktonic ones, detritus, periphyton, small benthic prey..…”
Section: Resultsmentioning
confidence: 99%
“…A similar situation (Margalef 1947;Alonso 1980) and in the spinicaudatan Leptestheriella madur~iensis (Royan 1976). From an experimental study, Mertens et al (1990) showed that Streptocephatus prosbocideus did not capture entomostraca offered and that fragments of crustaceans found in the gut content were ingested as cast exuviae.…”
Section: Discussionmentioning
confidence: 84%